Consumptive Behavior in Female University Students: Qana’ah and Hedonic Lifestyle as Predictors - Wulan Muawaliyah; Ahmad Saifuddin (Islamic Guidance and Counseling Journal, 2023)
Currently, many under graduate students are affected by consumptive behavior, so that consumptive behavior needs to be overcome, one of which is qana'ah behavior. Therefore, this study aimed to explain the correlation between qana'ah and a hedonic lifestyle with consumptive behavior in female students. The research method used was quantitative correlation study with a multiple regression analysis technique. There were three measuring tools used in this study, namely qana'ah scale, hedonic lifestyle scale, and consumptive behavior scale. Following a cluster random sampling approach, this study obtained a sample consisting 297 Universitas Islam Negeri (UIN) Raden Mas Said Surakarta female students aged 18-22 years old. The data analysis technique implemented in the present study was regression analysis resulting in F=151.488; R2=0.508; p<0.05. Partial analysis showed that qana'ah has a negative relationship with consumptive behavior, with a correlation coefficient of -6.415 (p <0.05), and hedonic lifestyle has a positive relationship with consumptive behavior, with a correlation coefficient of 13.570 (p <0.05). Qana’ah is negatively correlated with consumptive behavior, meaning that the higher the qana’ah level in oneself, the lower the prevalence of exhibiting consumptive behavior. Meanwhile, the hedonic lifestyle is found to be positively correlated with consumptive behavior. It means that when a person adopts a hedonic lifestyle, they are more likely to show consumptive behavior. Based on the analysis, there is a correlation between qana'ah and hedonic lifestyles with consumptive behavior in female students of UIN Raden Mas Said Surakarta. Thus, qana’ah can become a solution to reduce the level of consumptive behavior. In more serious cases, qana'ah can be made into therapy so that it becomes qana'ah therapy to reduce mental problems, one of which is consumptive behavior.